ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN ISU GENDER - Brahmasari, Ida Ayu (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
Organizational Citizenship Behavior (OCB) as an individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization, although discoursed in the literature as gender-neutral, gender is deeply embedded within the concept. This paper tries to explore OCB and its dimensions and its relation to gender. A number of argumentations suggest that two dimensions of OCB ( altruism and courtesy) alhought not exclusively, are stereotypically associated with womenâ€™s behavior, while three other dimensions of OCB ( sportsmanship, civic virtue and conscientiousness) highlight characteristics that are stereotypically associated with men.Â Keywords: organizational citizenship behavior, altruism, courtesy, sportsmanship, civic virtue, conscientiousness, gender